2008
DOI: 10.1021/jo702741n
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Stability of [60]Fullerene Cycloadducts:  Retro-Cycloaddition Reaction of 2-Pyrazolino[4,5:1,2][60]fullerenes

Abstract: 2-Pyrazolino[4,5:1,2][60]fullerenes undergo a thermally induced retro-cycloaddition process whose efficiency is influenced by the nature of the C-substituent. C-Aryl-N-Aryl-2-pyrazolino[60]fullerenes (2a-d) poorly undergo a thermal retro-cycloaddition reaction even in the presence of a strong dipolarophile or a metal Lewis acid which, in contrast to other fullerene derivatives, shows their remarkable thermal stability. C-Alkyl-N-Aryl-2-pyrazolino[60]fullerenes (2e-f) show a different behavior, being more vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…In agreement with the results obtained by mass spectrometry, 3-alkyl-2-arylpyrazolinofullerenes undergo an efficient retro-cycloaddition process when they are refluxed in ortho-dichlorobenzene (o-DCB) for 48 h in the presence of a strong dipolarophile such as maleic anhydride [24]. The presence in the thermal reaction of a metal salt in which metal cation possesses Lewis acid property (copper triflate) activates the retro-cycloaddition process increasing the obtained yields.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with the results obtained by mass spectrometry, 3-alkyl-2-arylpyrazolinofullerenes undergo an efficient retro-cycloaddition process when they are refluxed in ortho-dichlorobenzene (o-DCB) for 48 h in the presence of a strong dipolarophile such as maleic anhydride [24]. The presence in the thermal reaction of a metal salt in which metal cation possesses Lewis acid property (copper triflate) activates the retro-cycloaddition process increasing the obtained yields.…”
Section: Resultssupporting
confidence: 80%
“…Because C 60 acts as an electron poor olefin, the cycloaddition reaction with azomethine ylides leads to the formation of pyrrolidinofullerenes [22,23] while the dipolar cycloaddition of nitrile imines affords the corresponding pyrazolinofullerenes [24]. During the course of our investigations on the homo-and heterocyclic fullerene cycloadducts, we have observed that the molecular odd-electron ions generated under ESI conditions and negative mode of detection from substituted isoxazolinofullerenes [25] .…”
Section: Introductionmentioning
confidence: 91%
“…Indeed our new fullerene derivatives could be susceptible to retro-cycloaddition reactions as other fullerene cycloadducts. [41,42] In order to investigate this, we measured the and TBCB-Bis after being subjected to three DSC cycles did not display any detectable changes thereby reconfirming their superior thermal stability as compared to the TMCB multiadducts. To determine if crystallization might also be responsible for the exothermic DSC transitions of the TMCB multiadducts at high temperatures, we conducted X-ray diffraction experiments ( Figure S5 (a, b)).…”
Section: Thermal Propertiesmentioning
confidence: 93%
“…Significantly, in contrast to other fullerene derivatives, the resulting 2-pyrazolinefullerenes show better, or at least equivalent, electron affinity when compared to the parent C 60 and they also exhibit remarkable thermal stability. 22 Although numerous cycloaddition reactions have been explored experimentally with fullerenes 23 or carbon nanotubes, 24 and despite the fact that the covalent functionalization of graphene is a growing field of research, only the 1,3-dipolar cycloaddition of azomethine ylides 14,15 has been applied to the functionalization of graphene. [25][26][27][28] The band gap and the work function (WF) of a material provide information about the electronic states on the surface of the solid and most organic electronic devices require the use of semiconducting materials in which the work function should be adjustable, thus allowing efficient charge transport.…”
Section: Introductionmentioning
confidence: 99%